Perspective of Fe3O4 Nanoparticles Role in Biomedical Applications - Mohammad Reza Ghazanfari; Mehrdad Kashefi; Seyyedeh Fatemeh Shams; Mahmoud Reza Jaafari (Biochemistry Research International)
In recent years, although many review articles have been presented about bioapplications of magnetic nanoparticles by some research groups with different expertise such as chemistry, biology, medicine, pharmacology, and materials science and engineering, the majority of these reviews are insufficiently comprehensive in all related topics like magnetic aspects of process. In the current review, it is attempted to carry out the inclusive surveys on importance of magnetic nanoparticles and especially magnetite ones and their required conditions for appropriate performance in bioapplications. The main attentions of this paper are focused on magnetic features which are less considered. Accordingly, the review contains essential magnetic properties and their measurement methods, synthesis techniques, surface modification processes, and applications of magnetic nanoparticles.